Effectiveness of integrase strand transfer inhibitors in HIV‐infected treatment‐experienced individuals across Europe. Issue 7 (24th February 2022) - Rossetti, Barbara; Fabbiani, Massimiliano; Di Carlo, Domenico; Incardona, Francesca; Abecasis, Ana; Gomes, Perpetua; Geretti, Anna Maria; Seguin‐Devaux, Carole; Garcia, Federico; Kaiser, Rolf; Modica, Sara; Shallvari, Adrian; et al.
Abstract: Objectives: To explore the effectiveness and durability of integrase strand transfer inhibitor (INSTI)‐based regimens in pre‐treated subjects. Methods: Treatment‐experienced individuals starting an INSTI‐based regimen during 2012–2019 were selected from the INTEGRATE collaborative study. The time to virological failure [VF: one measurement of viral load (VL) ≥ 1000 copies/mL or two ≥ 50 copies/ml or one VL measurement ≥ 50 copies/mL followed by treatment change] and to INSTI discontinuation were evaluated. Results: Of 13 560 treatments analysed, 4284 were from INSTI‐naïve, non‐viraemic (IN‐NV) individuals, 1465 were from INSTI‐naïve, viraemic (IN‐V) individuals, 6016 were from INSTI‐experienced, non‐viraemic (IE‐NV) individuals and 1795 were from INSTI‐experienced, viraemic (IE‐V) individuals. Major INSTI drug resistance mutations (DRMs) were previously detected in 4/519 (0.8%) IN‐NV, 3/394 (0.8%) IN‐V, 7/1510 (0.5%) IE‐NV and 25/935 (2.7%) IE‐V individuals. The 1‐year estimated probabilities of VF were 3.1% [95% confidence interval (CI): 2.5–3.8] in IN‐NV, 18.4% (95% CI: 15.8–21.2) in IN‐V, 4.2% (95% CI: 3.6–4.9) in IE‐NV and 23.9% (95% CI: 20.9–26.9) in IE‐V subjects. The 1‐year estimated probabilities of INSTI discontinuation were 12.1% (95% CI: 11.1–13.0) in IN‐NV, 19.6% (95% CI: 17.5–21.6) in IN‐V, 10.8% (95% CI: 10.0–11.6) in IE‐NV and 21.7% (95% CI: 19.7–23.5) in IE‐V subjects. Conclusions: Both VF and INSTI discontinuation occur at substantial rates in viraemic subjects. Detection of DRMs in a proportion of INSTI‐experienced individuals makes INSTI resistance testing mandatory after failure.